Avaliação da contaminação de um rio utilizado para abastecimento humano por meio de biomarcadores de toxicidade - Storck, Tamiris Rosso (2020)
The contamination of water resources by pesticides is a growing environmental problem that can cause adverse effects on non-target organisms and, consequently, on the entire ecosystem. Pesticides used in agriculture can contaminate water resources, mainly through runoff, leaching and erosion processes. Brazil is one of the largest consumers of these chemicals, and the major destination for the sale of pesticides is for soybean crops. Among the Brazilian states, Rio Grande do Sul (RS) has an important participation in the country's agricultural production, with emphasis on the municipalities of the north-northwest region. Therefore, the aim of this study was to verify the presence of pesticides in the Potiribu River, in the municipality of Ijuí, located in the northwest of RS, and to evaluate the possible toxic effects of these on lambaris (Astyanax sp.) using toxicity biomarkers, in different periods of agricultural crops. Water, sediment and fish were sampled in three sites in the Potiribu River in the summer (end of January), autumn (beginning of June) and winter (beginning of September) of 2019. Regarding the physical-chemical variables of water, in general the worst quality was registered in summer and the best in winter. The pesticides clomazone, atrazine and imidacloprid were detected in the water in summer and winter, and clomazone and imidacloprid in autumn; only the pesticide fenpropimorph was detected in the autumn in the sediment. No pesticides were detected in the muscle of Astyanax sp. In the summer it was observed the highest levels of carbonyl proteins in the gills, higher levels of non-protein thiols in the liver and muscle of the fish, while in the gills, brain and intestine there were lower levels of non-protein thiols in this period. In the autumn, there was less activity of acetylcholinesterase in the muscle, greater activity of catalase in the liver, and higher levels of carbonyl proteins in all tissues. In winter, higher levels of lipid peroxidation were observed in the muscle and brain of fish, as well as glutathione S-transferase activity and non-protein thiol levels in the gills, brain and intestine. The responses obtained by biomarkers can be related both to the pesticides detected in the water and to the discharge of domestic sewage in the Potiribu River, and revealed the complexity of biomonitoring, considering the wide mixture of chemical compounds present in the water, combined with the abiotic variables.